2018
DOI: 10.1002/smll.201704008
|View full text |Cite|
|
Sign up to set email alerts
|

Exosomal miRNA Profiling to Identify Nanoparticle Phagocytic Mechanisms

Abstract: Inhaling a dangerous amount of nanoparticles leads to pulmonary inflammatory and immune disorders, which integrates several kinds of cells. Exosomes are suggested to play a crucial role in intercellular communication via miRNA transmission. To investigate the role of exosomal miRNA in nanoparticle phagocytosis, a total of 54 pneumoconiosis patients along with 100 healthy controls are recruited, exosomes derived from their venous blood are collected, and then exosomal miRNAs are profiled with high-throughput se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 44 publications
1
30
0
Order By: Relevance
“…Compared to healthy controls, relative expression levels of exosomal let-7a-5p in venous blood from pneumoconiosis patients was decreased by 21.67% (0.47 ± 0.24 vs. 0.60 ± 0.24, t = 3.11, P = 0.002) (Fig. 1b ), consistent with high throughput sequencing results shown in our previous study [ 8 ], suggesting that exosomal let-7a-5p may be involved in the development of pneumoconiosis.
Fig.
…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Compared to healthy controls, relative expression levels of exosomal let-7a-5p in venous blood from pneumoconiosis patients was decreased by 21.67% (0.47 ± 0.24 vs. 0.60 ± 0.24, t = 3.11, P = 0.002) (Fig. 1b ), consistent with high throughput sequencing results shown in our previous study [ 8 ], suggesting that exosomal let-7a-5p may be involved in the development of pneumoconiosis.
Fig.
…”
Section: Resultssupporting
confidence: 91%
“…Standard methods for exosome isolation and characterization have been previously described [ 8 ]. Briefly, five milliliters mixed serum was first diluted with 20-fold volume PBS and centrifuged at 2000 × g, 4 °C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exosomes consist of proteins, mRNA, and noncoding miRNA surrounded by a lipid bilayer membrane. [10][11][12][13] Further RNA forms including transfer RNA, ribosomal RNA, nucleolar RNA, and long noncoding RNA (lncRNA) have also been identified in exosomes. 14 Topical studies have demonstrated that fragments of DNA may exist in exosomes as well.…”
Section: Extracellular Vesiclesmentioning
confidence: 99%
“…For example, a recent study found that silica nanoparticle exposure‐induced inflammation and activated autophagy, which eventually lead to endothelial dysfunction in silicosis . For macrophages that were exposed to silica dust, it was suggested that MCPIP1 induced autophagy through the p53 signaling pathway, which could lead to cellular apoptosis and trigger the proliferation and trans‐differentiation of pulmonary fibroblast . Alternatively, several studies suggested that autophagy deficiency could aggravate lung damage …”
Section: Introductionmentioning
confidence: 99%